New model for predicting terminal settling velocity and drag coefficient of the Oncomelania - Liu, Xiaoguang; Wang, Jiasheng; Chai, Zhaohui; Min, Fengyang; Jiang, Xi; Zhu, Kongxian; Dai, Juan (Frontiers in Environmental Science, 2022)
This paper presents a study of the terminal settling velocity and drag coefficient of the Oncomelanias with highly irregular shape in the range of particle Reynolds number (10 < Rep < 600). The movement characteristics of the Oncomelanias with horizontal and slant postures are revealed using image analysis and wavelet analysis. The shape features of Oncomelanias with different dimensions are quantified and formulated. The authors propose a new model for predicting the drag coefficient of the dormant and active Oncomelanias, which is proven to be better than several widely-used formulas. Further, a simple settling velocity model that can predict the terminal velocity of the Oncomelanias fairly with several easy-to-measure parameters is developed. These findings provide a basis for the further improvement for the hydraulic schistosomiasis control project and supply reference for the settling characteristics and drag coefficient of cone-shaped particles.